GermVersity: A free and user-friendly interface to enhance the visualization and analysis of genebank data - Joaquin Guillermo Ramirez-Gil; Felipe López-Hernández; Diego Felipe Conejo-Rodriguez; Juan Camilo Henao-Rojas; Kevin Estiven Quiroga-Benavides; Andrés J. Cortés; Maria Isabel Chacón-Sánchez (PLoS ONE, 2026)
Genebanks are crucial for food security and industrial applications. However, their heterogeneous nature hinders effective utilization. To address this, the GermVersity platform was developed to integrate conventional, artificial intelligence, and data science approaches to the transversal analysis of data associated with genebank accessions. GermVersity aids in the classification and prioritization of germplasm diversity, facilitating the conservation and utilization of valuable genetic resources in agriculture. The GermVersity proposal is focused on developing a user-friendly application to visualize, analyze and interpret analysis-ready data from genebanks. The application’s case study uses data from the bean genebank at Bioversity International – CIAT but can be adapted for other genebanks and broader collections. GermVersity is divided into three modules. The first module analyzes genetic diversity using phenotypic and SNP data. In this module users can prioritize morphological descriptors for efficient classification of accessions, define genetic clusters or populations, calculate basic diversity statistics per locus and per population, and estimate genetic divergence among clusters or populations. The second module implements spatial distribution modeling, allowing users to understand ecological diversity across the geographical distribution range of a set of accessions. The third module characterizes the genomic architecture of phenotypic trait variation and adaptation to ecological niches using genome-wide association implemented in prediction integrated tools (GAPIT) and Latent Factor Mixed Model (LFMM) analysis. The GermVersity platform was built using Shiny-Golem and is hosted on GitHub for free use. To access it, users can install the library and run the application through specific commands in R. Responsible use of algorithms is recommended, along with the inspection of results for biological coherence. Ultimately, GermVersity offers an integrated analytical pipeline to leverage genebank diversity as part of pre-breeding efforts.